ТЕХНІКО-ЕКОНОМІЧНІ АСПЕКТИ ОЦІНЮВАННЯ ПЕРСПЕКТИВ ДЕКАРБОНІЗАЦІЇ ОБ’ЄДНАНОЇ ЕНЕРГОСИСТЕМИ УКРАЇНИ - Басок, Б.І.; Буткевич, О.Ф.; Дубовський, С.В. (Інститут електродинаміки НАН України, Київ, 2021)
Shot analysis of power systems decarbonisation problem to ensure a net-zero greenhouse gas emissions is given. The mathematical model of the power system capacity balancing, generating capacities of which are renewables and nuclear power plants (NPP) is proposed. For capacity balancing storage power plants (SPP) with specified efficiency indicators are used. By using the indicators of the operational conditions of the IPS of Ukraine in 2019 and mathematical modeling for various options of the NPP installed capacity in the decarbonised IPS of Ukraine, the needs in the renewables installed capacity and in the capacity and energy of various types of the SPP were estimated. References 10, figures 4, tables 2.